Evaluation of a SNP-STR haplotype panel for forensic genotype imputation. (January 2023) - Chen, Ji; Yang, Jiawen; Li, Kai; Ji, Qiang; Kong, Xiaochao; Xie, Sumei; Zhan, Wenxuan; Wu, Jiayi; Huang, Shuainan; Huang, Huijie; Li, Rong; Zhang, Zhiwei; et al.
Abstract: Short tandem repeat polymorphism (STR)-based individual identification is a popular and reliable method in many forensic applications. However, STRs still frequently fail to find any matched records. In such cases, if known STRs could provide more information, it would be very helpful to solve specific problems. Genotype imputation has long been used in the study of single nucleotide polymorphisms (SNPs) and has recently been introduced into forensic fields. The idea is that, through a reference haplotype panel containing SNPs and STRs, we can obtain unknown genetic information through genotype imputation based on known STR or SNP genotypes. Several recent studies have already demonstrated this exciting idea, and a 1000 Genomes SNP-STR haplotype panel has also been released. To further study the performance of genotype imputation in forensic fields, we collected STR, microhaplotype (MH) and SNP array genotypes from Chinese Han population individuals and then performed genotype imputation analysis based on the released reference panel. As a result, the average locus imputation accuracy was ∼83 % (or ∼70 %) when SNPs in the SNP array (or MH SNPs) were imputed from STRs, and was ∼30 % when highly polymorphic markers (STRs and MHs) were imputed from each other. When STRs were imputed from SNP array, the average locus imputation accuracy increased to ∼48 %. After analyzing the match scores between real STRs and the STRs imputed from SNPs, ∼80 % of studied STR records can be connected to corresponding SNP records, which may help for individual identification. Our results indicate that genotype imputation has great potential for forensic applications. Highlights: A novel study of performing genotype imputation across disjoint genetic marker sets based on a 1000 Genomes SNP-STR haplotype panel. Genotype imputation has great application potential for extracting genetic information associated with STRs. Match score analysis after genotype imputation may help for individual identification.